2017
DOI: 10.18632/oncotarget.22878
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cancer prognosis-associated functional modules using differential co-expression networks

Abstract: The rapid accumulation of cancer-related data owing to high-throughput technologies has provided unprecedented choices to understand the progression of cancer and discover functional networks in multiple cancers. Establishment of co-expression networks will help us to discover the systemic properties of carcinogenesis features and regulatory mechanisms of multiple cancers. Here, we proposed a computational workflow to identify differentially co-expressed gene modules across 8 cancer types by using combined gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…The high recurrence rate and drug resistance make the treatment of BC difficult in clinical research. Studies have shown that multiple genes always interact with each other to regulate the development of tumors [35]. m6A RNA methylation regulators play an important role in the development of cancer [36].…”
Section: Discussionmentioning
confidence: 99%
“…The high recurrence rate and drug resistance make the treatment of BC difficult in clinical research. Studies have shown that multiple genes always interact with each other to regulate the development of tumors [35]. m6A RNA methylation regulators play an important role in the development of cancer [36].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of retrofitted radiation therapy and targeted therapy, the 5‐year survival rate of patients has improved, but local recurrence and drug resistance brought difficulties in CESC treatment. Studies have shown that cancer progression can be regulated by the interaction of multiple genes, 18 and m6A RNA methylation regulators play significant roles in tumourigenesis and development 19 . Thus, it is necessary to explore the effects of m6A RNA methylation regulators on CESC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the present study attempted to predict the potential mechanisms of the role of HOXA11 in LUAD in silico . With the development of high-throughput sequencing and novel computational approaches, accumulating evidence has proven that multiple genes always function together and then regulate tumor initiation and progression ( 32 ). To investigate the function of HOXA11, the cBioPortal and MEM databases were used in the present study to identify the genes co-expressed with HOXA11.…”
Section: Discussionmentioning
confidence: 99%